Another Look at Moral Foundations Theory: Do Authoritarianism and Social Dominance Orientation Explain Liberal-Conservative Differences in “Moral” Intuitions? - Kugler, Matthew; Jost, John T.; Noorbaloochi, Sharareh (Social justice research, 2014)
Moral foundations theorists propose that the moral domain should include not only “liberal” ethics of justice and care but also ostensibly “conservative” concerns about the virtues of ingroup loyalty, obedience to authority, and enforcement of purity standards. This proposal clashes with decades of research in political psychology connecting the latter set of characteristics to “the authoritarian personality.” We demonstrate that liberal-conservative differences in moral intuitions are statistically mediated by authoritarianism and social dominance orientation, so that conservatives’ greater valuation of ingroup, authority, and purity concerns is attributable to higher levels of authoritarianism, whereas liberals’ greater valuation of fairness and harm avoidance is attributable to lower levels of social dominance. We also find that ingroup, authority, and purity concerns are positively associated with intergroup hostility and support for discrimination, whereas concerns about fairness and harm avoidance are negatively associated with these variables. These findings might lead some to question the wisdom and appropriateness of efforts to “broaden” scientific conceptions of morality in such a way that preferences based on authoritarianism and social dominance are treated as moral —rather than amoral or even immoral—and suggest that the explicit goal of incorporating conservative ideology into the study of moral psychology (in order to increase ideological diversity) may lead researchers astray.